2015
DOI: 10.1186/s12944-015-0015-4
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of fatty acids from krill oil, krill meal and fish oil in healthy subjects–a randomized, single-dose, cross-over trial

Abstract: BackgroundKrill contains two marine omega-3 polyunsaturated fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), mainly bound in phospholipids. Typical products from krill are krill oil and krill meal. Fish oils contain EPA and DHA predominantly bound in triglycerides. The difference in the chemical binding of EPA and DHA has been suggested to affect their bioavailability, but little is known on bioavailability of EPA and DHA in krill meal.This study was undertaken to compare the acute bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 20 publications
3
68
0
Order By: Relevance
“…Earlier, we demonstrated variability of bioavailability of EPA and DHA as a triglyceride in a convenience drink by a factor of 13 inter-individually [20]. In the meantime, however, this has been confirmed by us, and others [47,67]. While predicting a mean dose-response of the Omega-3 Index to supplementation with EPA and DHA in a population using complicated statistical models is possible, such prediction is basically impossible for an individual [20,47,67].…”
Section: Discussionsupporting
confidence: 67%
“…Earlier, we demonstrated variability of bioavailability of EPA and DHA as a triglyceride in a convenience drink by a factor of 13 inter-individually [20]. In the meantime, however, this has been confirmed by us, and others [47,67]. While predicting a mean dose-response of the Omega-3 Index to supplementation with EPA and DHA in a population using complicated statistical models is possible, such prediction is basically impossible for an individual [20,47,67].…”
Section: Discussionsupporting
confidence: 67%
“…Dietary absorption might be affected by different formulations of omega-3 PUFAs, e.g. the bioavailability of triglyceride-associated PUFAs predominant in fish oil is reportedly lower than phosphoglyceride-associated PUFAs in as in krill oil (92). However, krill meal, which also contains DHA and EPA bound to phospholipids, has similar bioavailability to fish oil, suggesting the triglyceride-phospholipid difference may not be the main arbiter of absorption (92).…”
Section: Discussionmentioning
confidence: 99%
“…the bioavailability of triglyceride-associated PUFAs predominant in fish oil is reportedly lower than phosphoglyceride-associated PUFAs in as in krill oil (92). However, krill meal, which also contains DHA and EPA bound to phospholipids, has similar bioavailability to fish oil, suggesting the triglyceride-phospholipid difference may not be the main arbiter of absorption (92). Free (unesterified) fatty acids also have been suggested to have superior bioavailability (93) but are a target for oxidation that may result in breakdown and in gastrointestinal side-effects (94).…”
Section: Discussionmentioning
confidence: 99%
“…These results clearly show that phospholipid-rich krill oil behaves quite differently from other triacylglycerol-rich oils under simulated stomach conditions, which may have important implications for its gastrointestinal fate. Indeed, in vivo studies have reported higher bioavailability of omega-3 fatty acids when delivered as krill oil rather than as fish oil, which was partly attributed to the fact that the polyunsaturated fatty acids were part of phospholipids in krill oil(Kohler, Sarkkinen, Tapola, Niskanen, & Bruheim, 2015;Schuchardt et al, 2011). Conversely, other in vivo studies have reported a higher bioavailability of polyunsaturated fats from fish oils than from krill oil(Tou, Altman, Gigliotti, Benedito, & Cordonier, 2011).…”
mentioning
confidence: 99%